Knowledge Science, Engineering and Management 7th International Conference, KSEM 2014, Sibiu, Romania, October 16-18, 2014. Proceedings - Buchmann, Robert; Kifor, Claudiu Vasile; Yu, Jian (Lecture Notes in Artificial Intelligence, 2014)
This book constitutes the refereed proceedings of the 7th International Conference on Knowledge Science, Engineering and Management, KSEM 2014, held in Sibiu, Romania, in October 2014. The 30 revised full papers presented together with 5 short papers and 3 keynotes were carefully selected and reviewed from 77 submissions. The papers are organized in topical sections on formal semantics; content and document analysis; concept and lexical analysis; clustering and classification; metamodeling and conceptual modeling; enterprise knowledge; knowledge discovery and retrieval; formal knowledge processing; ontology engineering and management; knowledge management; and hybrid knowledge systems.